Um bispo no Concílio Vaticano II. Dom Geraldo de Proença Sigaud e o Coetus Internationalis Patrum - Caldeira, Rodrigo Coppe (Revista eclesiástica brasileira, 2011)
The late Archbishop of Diamantina, Don Geraldo de Proença Sigaud (1909-1999) was an important and controversial historical figure in the contemporary Brazilian Church. Indeed, Sigaud played a remarkable role in the polemical issues that pervaded the Church from the 1930s until 1980. Moreover, the Archbishop was one of the most important catalytic agents of the minority in the Vatican II Council (1962-1965), congregating around himself bishops with conservative tendency from all over the world in order to block the reform impetuses that were establishing themselves from the earliest conciliar period. Thus, from a historical perspective, the present article aims at presenting D. Sigaud’s actions at the Vatican II, his relations with the TFP (Association for the Defense of Tradition, Family and Property) at the time of the Council and to show some moments in the acting of the Coetus Internationalis Patrum, a group that Sigaud founded with other bishops in order to organize the Council’s minority and influence its final decisions.